The Capacity of Kulon Progo Regency Government in Efforts to Self-Sustaining Economic - Yovi Dzulhijjah Rahmawati (Pusbindiklatren Bappenas, 2020)
As an area with an open economic access, Kulon Progo Regency has many valuable points in the development of its agriculture, manufacturing, trade and services sectors. However, low level of the district public welfare becomes an internal strategic issues that affects its planning process. In the meantime, Kulon Progo District has its own leadership potential with good regional coordination and clear communication with its regional leaders. This potential can be a key element of its regional development as to reduce its internal issues. This leadership type owns by the regional leaders, along with the effective bureaucracy, is a manifestation of the capacity of its regional jurisdiction. This capacity of the Kulon Progo regency government within the framework to achieve self-sustaining economic can be obtained with the following efforts: (1) efforts to mobilize stakeholders in achieving self-sustaining economic by local leaders, (2) determination of local-pro economic policy and priorities program, and (3) implementation of a performance-based planning and budgeting process in an effort to boost the local economy. In practice, the leadership innovation is not strong enough to change the planning and budgeting system that has been institutionalized bureaucratically. Contextual conditions do have great affect to the success of leadership, policy making, and planning and budgeting aspects. Therefore, this study aims to examine the Kulon Progo District Government capacity in encouraging the self-sustaining economy.